Costos de generación, inversión y precios del sector eléctrico en México - Alejandra Enríquez; José Carlos Ramírez; Juan Rosellón (Investigación Económica, 2019)
– Electricity prices have seen a consistent upward trend since the implementation of Mexico's electricity market reform (EMR). This has been interpreted by some as a failure of the EMR. In this paper we study the determinants of such price increases. We calculate the generation cost curve of the Federal Electricity Commission prior to the entry into force of the reform. We then construct daily data on average prices during the EMR. We also finally study the relationship between prices and transmission congestion rents. Our main results indicate that the most profitable types of generation technology are the ones resulting from the EMR. Likewise, price increases have taken place despite the existence of a considerably larger number of competitors in the generation sector. Lastly, the strong correlation between prices and congestion revenues is evidence that the increase in prices under the EMR is mainly due to the growing congestion in the national electricity transmission network rather than due to an inefficient competitive market design in the generation sector.
Keywords: D21; D47; L50; L51; Q41; 330; Electricity reform; electricity generation; congestion rents; nodal prices; Mexico